(untitled) (Research, Society and Development, 2020)
Betahydroxy-beta-methylbutyrate (HMB) is a branched-chain metabolite of the amino acid L-Leucine, synthesized in liver and muscle cells. It shows many functional properties observed as therapeutic effect in many deseases, highlighting those with proteic catabolism nd anticatabolic effect, being related to the increase of muscle strength and muscle mass, therefore, without treatment of sarcopenia. This study is a literature review not classified as PubMed, eduCAPES, ResearchGate database with keywords "beta-hydroxy-beta-methylbutyrate" or "HMB", "anabolic effect of HMB", "dietary sources" properties of HMB". The terms were designated, those that prevail are a factor of differentiation and the therapeutic and functional factors, standing out their anabolic effect, increase of the strength and reduction of the body fat.